Health care patterns and policies in 18 European countries during the first wave of the COVID-19 pandemic: an observational study. (27th May 2022) - Panteli, Dimitra; Reichebner, Christoph; Rombey, Tanja; Berger, Elke; Winkelmann, Juliane; Eckhardt, Helene; Nimptsch, Ulrike; Busse, Reinhard
Abstract: Background: The coronavirus disease 2019 (COVID-19) pandemic has developed into an unprecedented global challenge. Differences between countries in testing strategies, hospitalization protocols as well as ensuring and managing ICU capacities can illustrate initial responses to a major health system shock, and steer future preparedness activities. Methods: Publicly available daily data for 18 European countries were retrieved manually from official sources and documented in an Excel table (March–July 2020). The ratio of tests to cases, the share of hospitalizations out of all cases and the share of ICU admissions out of all hospitalizations were computed using 7-day rolling averages per 100 000 population. Information on country policies was collected from the COVID-19 Health System Response Monitor of the European Observatory on Health Systems and Policies. Information on health care capacities, expenditure and utilization was extracted from the Eurostat health database. Results: There was substantial variation across countries for all studied variables. In all countries, the ratio of tests to cases increased over time, albeit to varying degrees, while the shares of hospitalizations and ICU admissions stabilized, reflecting the evolution of testing strategies and the adaptation of COVID-19 health care delivery pathways, respectively. Health care patterns for COVID-19 at the outset of the pandemic did not necessarily follow the usual health service delivery pattern of each health system. Conclusions: This study enables a general understanding of how the early evolution of the pandemic influenced and was influenced by country responses and clearly demonstrates the immense potential for cross-country learning.